Analytical model for partially prestressed concrete beam-column elements - Esfahani, Milad Hafezolghorani (2017)
Nowadays, the demand for buildings and bridges with long span and light weight capable of withstanding any type of dynamic loading is increasing. The application of partially prestressing technique to reduce the yielding and damages in concrete members and structures offers an alternative solution to conventional reinforced concrete (RC) or fully prestressed concrete (FPC) approaches. Although partially prestressed concrete (PPC) has been widely used as a simple and economical construction technique for structures with medium to large span, there are no proper analytical and numerical models and detailed building code provisions for PPC elements. Besides, based on an extensive review of the literature, there is less information available about the possibility of identifying the damage in partially prestressed concrete beams and frame structures during earthquake excitation. Hence, in this study a new analytical model for PPC frame elements subjected to static and dynamic loads is developed. For this purpose, constitutive law and mathematical model for the three dimensional PPC beam-column element are formulated and a special finite element algorithm is developed. In order to develop three-dimensional nonlinear finite element formulations, the PPC frame element is represented by two nodes and an elastic element in between to reflect the elastic behavior of the member and two plastic hinges at each end of the member to reflect the inelastic behavior of the member. The elastic stiffness matrix of a three- dimensional PPC beam-column element with two nodes was developed during the present study; meanwhile, the elasto-plastic stiffness matrix of the three-dimensional PPC frame element having plastic hinges at both ends was derived using plasticity theory. Therefore, in order to detect the damages and determine the location of plastic hinges during dynamic loading in element, formulation for plasticity and yielding surface mechanism of PPC frame element is derived. A third degree polynomial using regression analysis was fitted to the results obtained from PPC section analysis to represent the mathematical model of the yield surface for each section. The developed analytical model and plasticity theory were codified and implemented in a special finite element program named ARCS3D in order to perform inelastic static and dynamic analysis for PPC structures. In order to validate the developed analytical model, plasticity formulation and the developed FE computer program code, five conventional RC and PPC beams and frames were fabricated and tested experimentally for cyclic load using dynamic actuator. The results showed a good correlation between the numerical analysis and the experimental tests. Several parametric studies were also undertaken for low-rise, medium-rise, and high-rise partially prestressed concrete framed buildings subjected to 2D nonlinear pushover and time history analysis. Furthermore, nonlinear pushover analysis was conducted on three-dimensional four-story RC and PPC buildings. Also, 3D nonlinear dynamic time history analysis was performed on the four-story RC and PPC frame buildings subjected to multi-directional EL-Centro earthquake accelerations. The functionality and effects of PPC buildings were then interpreted from different perspectives, such as variation of displacements, peak accelerations and plastic hinge formation. The results of numerical and experimental models indicated that application of the partially prestressed concrete members in structural systems effectively increased the strength and safety of the structure during dynamic loading. Also, the developed FEM program was able to successfully identify damage occurrence in PPC structural element during applied dynamic loads. To be more specific, a comparison between results shown that the ultimate capacity, degree of flexibility and energy dissipation capacity of the PPC beam specimens improved up to 70 %, 93 % and 300 % compared to the conventional RC beam specimen. From the experimental PPC frame results, the lateral load capacity and stiffness improved up to 34 % and 17 % compared to the RC frame. Also, no crack happened in the beam of the PPC frame under super imposed dead load. Furthermore, based on the parametric studies, application of PPC members in multi-storey concrete buildings subjected to seismic loads indicated a noticeable delay in the failure process, however, conventional RC buildings collapsed at the first stage of analysis. Ultimately, this study facilitates the analysis and design procedures of the multi-story PPC and RC buildings as well as bridges in an efficient computation time which is more economical compared to normal design methods.